1973
DOI: 10.2307/1540014
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF JUVENILE HORMONE ANALOGUES ON THE METAMORPHOSIS OF BEETLESTROGODERMA GRANARIUM(DERMESTIDAE) ANDCARYEDON GONAGRA(BRUCHIDAE)

Abstract: EFFECTS OF JUVENILE HORMONE ANALOGUES ON THE METAMORPHOSIS OF BEETLES TROGODERM. I GRANARITM ( DERMESTIDAE) AND CARYEDOX CONAGRA (BRl'CIIIDAE) AIOXIK M. METWALLYi AND FRANTISEK SEHXAI. Institute of Eiitninoloi/y, Czechoslovak . Icadeiny of Sciences, I'r Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Thus in T.granarium while Metwally and Sehnal (1973) found that only the early part of the life of the last larval instar is sensitive to juvenoid action, Srivastava and Srivastava (1974) in the same insect and Ishaya and Yablonski (1976) in Tribolium castaneum reported that the period of sensitivity extends to almost the end of the life of the instar. Similarly while Bhatnagar-Thomas (1972) and Metwally and Sehnal (1973) could not correlate the dose of juvenoid with the number of supernumerary moults in T.granarium, Srivastava and Srivastava (1974) found a direct relationship between the two. Metwally and Sehnal (1973) did not report growth in supernumerary instars but Bhatnagar-Thomas (1972), Srivastava and Srivastava (1974) and Ishaya and Yablonski 0976) noted such growth.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus in T.granarium while Metwally and Sehnal (1973) found that only the early part of the life of the last larval instar is sensitive to juvenoid action, Srivastava and Srivastava (1974) in the same insect and Ishaya and Yablonski (1976) in Tribolium castaneum reported that the period of sensitivity extends to almost the end of the life of the instar. Similarly while Bhatnagar-Thomas (1972) and Metwally and Sehnal (1973) could not correlate the dose of juvenoid with the number of supernumerary moults in T.granarium, Srivastava and Srivastava (1974) found a direct relationship between the two. Metwally and Sehnal (1973) did not report growth in supernumerary instars but Bhatnagar-Thomas (1972), Srivastava and Srivastava (1974) and Ishaya and Yablonski 0976) noted such growth.…”
Section: Introductionmentioning
confidence: 92%
“…Similarly while Bhatnagar-Thomas (1972) and Metwally and Sehnal (1973) could not correlate the dose of juvenoid with the number of supernumerary moults in T.granarium, Srivastava and Srivastava (1974) found a direct relationship between the two. Metwally and Sehnal (1973) did not report growth in supernumerary instars but Bhatnagar-Thomas (1972), Srivastava and Srivastava (1974) and Ishaya and Yablonski 0976) noted such growth.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, according to this view, in order to be effective an increased titre of JH{JHA should be available in the insect system and it should start action before the process of cellular differentiation is set into motion, probably at a time when the gene sets are being reprogrammed for a new developmental cycle. Metwally and Sehnal (1973) have observed that even the most severely affected specimens of Trogoderma resulting from pupal treatment, displayed slightly pigmented eyes, outlines of segmentation of appendages, and most important of these, the absence of pupal hair. The maximally affected individuals of Caryedon also resembled normal pupae except that their eyes and appendages showed adultlike differentiation.…”
Section: Morphogenetic Response In Relation To Dosementioning
confidence: 99%
“…In S. bullata, Srivastava and Gilbert (1969) noted that the thorax is the first to become refractory to hormone during pharate adult life followed by the head and then the abdomen. Gilbert and Schneiderman (1960) in A. polyphemus and Metwally and Sehnal (1973) in T. granarium and C. gonagra found that external genitalia and the abdomen as a whole were the first sensitive parts, then the thoracic structures and finally the appendages and mouth parts. In many species of endopterygotes, Slama (1971) had noted that the epidermal cells of the wing lobes, thoracic and head appendages, and external genitalia lose their sensitivity to juvenoids sooner than the epidermal cells of abdomen.…”
Section: Morphogenetic Response In Relation To Dosementioning
confidence: 99%
See 1 more Smart Citation